EFFECT OF SALT STRESS ON SEED GERMINATION, PHYSIOLOGICAL AND BIOCHEMICAL PARAMETERS OF VIGNA RADIATA AND VIGNA MUNGO (International Association of Biologicals and Computational Digest, 2023)
The response of two bean cultivars – Vigna radiata and Vigna mungo against four different salinity levels namely 0, 50, 100 and 150 mM NaCl were studied at germination and early seedling stage. This investigation was performed as laboratory experiment under completely randomized design (CRD) with three replications for each salinity level. The effect of salt stress on various Germination, Physiological and Biochemical parameters was observed. The results indicated the adverse effect of salt stress on all the studied parameters in both the cultivars. The maximum adverse effect was seen on the seeds under 150 mM NaCl treatment. The results also concluded that V. radiata is comparatively more tolerant to salt stress than V. mungo.
Keywords: Salt stress; Seed Germination; Protein; Starch; Reducing Sugar; Vigna radiata; Vigna mungo